OPTIMASI PADAT PENEBARAN LARVA IKAN PATIN SIAM (Pangasius hypophthalmus) PADA PEMELIHARAAN SISTEM INTENSIF - Didik Ariyanto; Evi Tahapari; Bambang Gunadi (Universitas Gadjah Mada, 2008)
The goal of this activity was to improve the productivity of Siamese catfish (Pangasius hypophthalmus) backyard hatchery. The research was conducted to identify the optimum density of larvae in the intensive rearing system. Two days post hatching larvae of P. hypophthalmus reared in 18 fiberglass containers size 40x30x30 cm3. The treatment used was 50, 100 and 150 fishes/litre in 6 replicates. A water recirculation system was used in this study and a hi-blower aeration system for oxigen supplay was added in it. The result showed that the density of larvae was not significant difference (P<0,05) for the survival rate at day-30, i.e. 21.34%; 19.78% and 19.71% for 50, 100 and 150 fishes/litre density of larvae, respectively. But the density of larvae was significant difference (P>0,05) for body weight at day-30, i.e. 0.47; 0.34 and 0.25 g/fishes for 50, 100 and 150 fishes/l, respectively.